2017
DOI: 10.3892/ol.2017.7681
|View full text |Cite
|
Sign up to set email alerts
|

STAT3 promotes the proliferation and migration of hepatocellular carcinoma cells by regulating AKT2

Abstract: Abstract. The aim of the present study was to investigate the correlation of STAT3 and AKT in HCC cells. HCC cells were transfected with si-STAT3 and si-AKT2 in vitro and the mRNA expression of STAT3 and AKT was detected by RT-PCR, and the protein expression was measured by western blot. MTT assays were used to evaluate cell proliferation, and Transwell assays were performed to detect the ability of migration and invasion. The relationship between STAT3 and AKT was analyzed by ChIP and Dual-luciferase reporter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 22 publications
0
21
0
2
Order By: Relevance
“…Zhang and colleagues demonstrated that STAT3 performs this function by regulating the expression of AKT2 [65]. HCC cells transfected with STAT3-specific small interfering RNAs (siRNAs) induced a downregulation of AKT2 expression along with its target genes, leading to a significant reduction in the invasive properties of the cells in vitro [65]. The direct crosstalk between the JAK/STAT and PI3K/Akt2 pathway further supports the role of STAT3 in promoting invasion and metastasis in HCC.…”
Section: Stat3 In Invasion and Metastasismentioning
confidence: 96%
See 2 more Smart Citations
“…Zhang and colleagues demonstrated that STAT3 performs this function by regulating the expression of AKT2 [65]. HCC cells transfected with STAT3-specific small interfering RNAs (siRNAs) induced a downregulation of AKT2 expression along with its target genes, leading to a significant reduction in the invasive properties of the cells in vitro [65]. The direct crosstalk between the JAK/STAT and PI3K/Akt2 pathway further supports the role of STAT3 in promoting invasion and metastasis in HCC.…”
Section: Stat3 In Invasion and Metastasismentioning
confidence: 96%
“…Furthermore, STAT3 may promote the invasiveness of HCC by regulating alternative oncogenic pathways involved in metastasis. One such pathway is the PI3K/Akt2 signaling pathway, which modulates cell adhesion and invasion both in vitro and in vivo [64,65]. Zhang and colleagues demonstrated that STAT3 performs this function by regulating the expression of AKT2 [65].…”
Section: Stat3 In Invasion and Metastasismentioning
confidence: 99%
See 1 more Smart Citation
“…When HCC cell lines (SMMC7721 and QGY-7703) were transfected with siRNA targeting STAT3 and AKT2, a significant decrease in the mRNA level of AKT2 and STAT3 was observed. Furthermore, nude mice were used to verify the correlation, and a decreased ability for HCC cell proliferation, migration and invasion has been since concluded [ 119 ].…”
Section: Tackling the Crosstalk Between The Tumor And Its Microenvmentioning
confidence: 99%
“…The high expression of TBC1D3 was associated with decreased STAT3 phosphorylation in recipient cells(Qin et al 2019). A decreased phosphorylated level of STAT3 was found to inhibit the proliferation and migration of HCC(Xie et al 2018). Consistently in this study, the incubation of Hep3B cells in conditioned media of siRNA STC1 -transfected M1-polarized cells showed a significant reduction in cell motility.…”
mentioning
confidence: 95%